2015
DOI: 10.1177/0194599815596341
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraoperative versus Postoperative Parathyroid Hormone Levels to Predict Hypocalcemia Earlier after Total Thyroidectomy

Abstract: Intraoperative PTH has no significant disadvantage versus early postoperative PTH when used as a clinical guide for discharge after thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
1
34
0
2
Order By: Relevance
“…Postoperative PTH serum levels may accurately predict occurrence as well as severity of hypocalcaemia after thyroidectomy . Numerous studies have utilized either absolute values or relative percentage decrease of PTH for diagnosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative PTH serum levels may accurately predict occurrence as well as severity of hypocalcaemia after thyroidectomy . Numerous studies have utilized either absolute values or relative percentage decrease of PTH for diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative PTH serum levels may accurately predict occurrence as well as severity of hypocalcaemia after thyroidectomy. [17][18][19][20][21][22][23][24][25][26] Numerous studies have utilized either absolute values or relative percentage decrease of PTH for diagnosis. 20,[27][28][29][30][31][32] In addition, timing for PTH measurements varies significantly among studies, ranging from intraoperative measurements to measurements in the early postoperative period (generally 1-4 hours after surgery) up to 24 hours postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The half-life of PTH is 3 minutes and its measurement is a very accurate predictor of subsequent hypocalcemia (30). It appears to be no disadvantage using intraoperative PTH measurement versus that obtained postoperatively to guide initial clinical management of serum calcium (31). In our study, PTH following surgery differed significantly between the two groups of patients.…”
Section: Discussionmentioning
confidence: 53%
“…In the review of Grodski and Serpell,14 it was concluded that PTH measurement varies from 10 minutes postoperatively to several hours, which would provide equally accurate results. Lee et al15 concluded in a meta-analysis that intraoperative PTH has no significant advantage over early postoperative PTH when used as a clinical guide for discharge after thyroidectomy. In our study, PTH, measured in the next morning after surgery, presented an excellent predicting and discriminative ability.…”
Section: Discussionmentioning
confidence: 99%